2016
DOI: 10.1136/bcr-2016-216704
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal bronchogenic cyst mimicking congenital lobar emphysema

Abstract: Bronchogenic cyst (BC) is a rare congenital malformation of the lung. Most patients remain asymptomatic until adulthood while some are symptomatic in the first few years of life. However, symptoms in newborn period are rare. We report a case of a 3-day-old preterm baby with respiratory distress diagnosed as congenital lobar emphysema on chest X-ray. A CT scan revealed a mediastinal cyst causing obstructive lobar emphysema. The cyst was excised and pathological examination was suggestive of BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Esophageal symptoms (particularly feeding problems), critical airway obstruction, and severe lower respiratory symptoms (cough, fever, dyspnea, and hypoxia) were the most common clinical presentations in the enrolled patients, in line with previously reported case reports and case series [ 2 , 3 , 4 , 7 , 8 , 11 , 12 , 13 , 14 ]. In cases 1 and 3, the patients presented with recurrent cough and choking since the second week of life, and dynamic airway compression mimicking congenital lobar emphysema (CLE).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Esophageal symptoms (particularly feeding problems), critical airway obstruction, and severe lower respiratory symptoms (cough, fever, dyspnea, and hypoxia) were the most common clinical presentations in the enrolled patients, in line with previously reported case reports and case series [ 2 , 3 , 4 , 7 , 8 , 11 , 12 , 13 , 14 ]. In cases 1 and 3, the patients presented with recurrent cough and choking since the second week of life, and dynamic airway compression mimicking congenital lobar emphysema (CLE).…”
Section: Discussionsupporting
confidence: 89%
“…For instance, Arun et al reported a 3-day-old neonate who had severe respiratory distress, where the plain chest X-ray revealed CLE. Prior to the surgery, a chest CT scan was performed, which revealed a BC compressing the main-stem bronchi, causing severe air trapping and mimicking the CLE diagnosis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of diagnostic modalities is available for the detection of bronchogenic cysts [2,8]. These techniques are mainly radiological and include magnetic resonance imaging (MRI) and computed tomography (CT) [6,13]. Other invasive diagnostic strategies can be used, such as fine-needle aspiration or excisional tissue examination, which is considered the most accurate diagnostic method [8,20].…”
Section: Diagnosis Of Bronchogenic Cystsmentioning
confidence: 99%
“…This can significantly reduce the incidence of complications [5]. Yet, surgical intervention may be associated with complications in cases where cysts are adherent to surrounding tissue, making total excision more challenging [6,19]. In such situations, the remaining part of the cyst can lead to flare-up attacks or other complications in the long term, which favors conservative therapy [14].…”
Section: Management Of Bronchogenic Cystsmentioning
confidence: 99%
See 1 more Smart Citation